Antecedents of customer value co-creation in Islamic banking: The role of religiosity, perceived value and behavioral factors - Abror Abror; Dina Patrisia; Yunita Engriani; Nazirul Mubin Bin Mohd Noor; Maznah Wan Omar; Muhd. Al Hafizh; Vanessa Gaffar; Muthia Roza Linda (Cogent Business & Management, 2023)
This study aims to examine some antecedents of customer value co-creation in the Islamic bank industry. It also addresses the role of religiosity, perceived value and behavioral factors on customer value co-creation. This quantitative study used 400 respondents as the sample. Data were collected through survey and after some preliminary analyses, this study analyzed 390 responses in the main analysis. Data were analyzed using Covariance Based Structural Equation Modeling (CB-SEM) with AMOS 24 as the software package. The result indicates that several factors affect customer value co-creation, including religiosity, service quality, perceived value and customer commitment. Even though there is no significant direct relationship between satisfaction and customer value co-creation, it was found that satisfaction relates to customer value co-creation through customer commitment as the mediator. This study also found the moderating role of religiosity on the relationship between customer satisfaction and customer commitment. Limitations and future research are discussed.
Keywords: 650; customer commitment; customer value co-creation; perceived value; religiosity; satisfaction